Trimalchio’s Last Will: Shifting Inter-Actions between Seeming and Being - Köstner, Elena (Journal of Historical Network Research, 2019)
During the cena Trimalchionis – maybe the most prominent stage of Petronius Satyrica – we come to know of different testamentary dispositions whereby the focus is set on Trimalchio as legatee, heir, and especially as testator. To analyze and visualize these different roles here, I used an approach derived from historical network research: the ego-alter-dyad enables a systematic analysis of interpersonal interactions which can be regarded as the basis of most Roman last wills. The testament in Rome, in the sense of a last will and testament, implied a unilateral disposal by which an heir was appointed, or a person intended by law to be an heir was excluded from inheritance. Apart from the legal context a testament was also regarded as ultimate as well as financial confirmation of amicitia and family ties. Using the approach derived from historical network research the ties connecting Trimalchio with his former patronus, friends, family members, and slaves are visualized in different graphs. It is the aim of this paper bringing both sources and graphs into dialog and interpret them together. By doing so, Trimalchio’s mimus which he performed when reading out his last will gets obvious. He did not reply any of his mutual friendship or family ties in his testament, but he makes his friends and family members believe he would do so. Thereby, Trimalchio offended against a societal norm which was of paramount importance in Roman society. In his cena Trimalchionis Petronius creates a bizarre mimus where the dramatis personae, especially Trimalchio, were shifting between authenticity and illusion, between seeming and being.